Understanding racial disparities in pretrial detention recommendations to shape policy reform - Skeem, Jennifer L. (Criminology & public policy, 2023)
Research Summary Federal pretrial services and probation officers assess defendants and make influential recommendations that defendants be either released or detained, based on their threat to community safety and risk of flight. To inform efforts to reduce disparities in pretrial detention, we examined officers’ decision making about 149,815 defendants across 81 districts. Overall, the probability of a detention recommendation was 34% higher for Black than White defendants. Racial disparities were most pronounced in ambiguous cases that invoked substantial officer discretion - including cases where the defendant had little or no criminal record. Nevertheless, mediation analyses revealed that up to 79% of the racial disparity in detention recommendations operates through institutionalized factors (i.e., pretrial policy) rather than personally mediated factors (e.g., implicit racism or classism). The lion's share of the disparity operates through one institutionalized factor alone: criminal history. Policy Implications This study illustrates an empirical strategy for understanding the pathways through which disparities operate, which is crucial for shaping effective solutions. Providing officers with training and decision guides could reduce personally mediated bias - which is crucial for high discretion cases. However, this study shows that disparities mostly flow through institutionalized bias. So, greater gains may be had by making strategic shifts in policies and their implementation. One promising direction is to corral criminal history by adopting a tight definition that demonstrably predicts violence and failure to appear, and limiting the weight assigned to criminal history versus other predictive factors, when making recommendations. Another promising direction is to adopt risk-based release policies that leverage an existing tool to reduce both detention rates and racial disparities.